Why a Stubborn Conservative would Run a Deficit: Policy with Time- Inconsistent Preferences - Persson, Torsten; Svensson, Lars E. O. (Quarterly Journal of Economics, 1989)
A conservative government, in favor of a low level of public consumption, knows that it will be replaced by a government in favor of a larger level of public consumption. We show that the resulting level of public consumption is in between the levels the two governments would choose if each were in power both in the present and in the future. In particular, we show that if the conservative government is more stubborn (in a particular sense) than the succeeding government, the conservative government will borrow more than it would had it remained in power in the future.